EVALUASI KETERSEDIAAN INFRASTRUKTUR JALUR PEJALAN KAKI DI UNIVERSITAS INDONESIA - Surya, Muhammad Safarudin; Sumabrata, Jachrizal; Tjahjono, Tri (FSTPT Indonesia, 2015)
Walking is one of the short distance transportation activities for students of Universitas Indonesia. However, all around the campus there are still some pedestrian paths that are less maintained and connection-less than the rest. Knowing the existing condition of the current pedestrian infrastructure, factor in to the evaluation of the pedestrian pathways. This evaluation is necessary to determine the factors that influence the willingness of students to walk. This study uses survey and direct observation through the questionnaire given to the students of Universitas Indonesia. The results of the analysis based on the respondents' assessment variables for pedestrian infrastructure, indicates that the variable most influential is the facility itself, with a significance value below 0.01. As for the desire to walk away, the reliability of the walk way is the most influential variable with the significance values ​​below 0.01.